Manajemen Pendidikan Karakter dalam Mewujudkan Peserta Didik yang Berakhlakul Karimah - Laeli, Nur (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2022)
This research is motivated by the importance of character problems in students who are stillinadequate. In this regard, this study aims to determine the management of characterformation to realize the morals of students at MI Al-Muttaqin Binangun. This research is aqualitative type. Data collection through interviews, observation and documentation. Thevalidity of the data using triangulation. Data analysis techniques include data reduction, datadisplay, and drawing conclusions. This study resulted in five conclusions: (1) Charactereducation planning is carried out through joint deliberations to determine the character andmoral values to be developed. And after the plan is completed, the next step is to instill valuesand morality in students that aim to strengthen character education. These values and moralsare in line with the vision and mission of the madrasa. These values and morals include:religious, sincere, hardworking, intelligent and caring. (2) Organizing character education,where the teacher becomes a role model for madrasah students is going well. These valuesand morals are implemented in different ways depending on the style of each teacher. (3)Character education directives include activities that improve teacher-student relationships,provide opportunities for students to voice their opinions, and motivate students. (4) Controlof character education is carried out by equipping students with the development of moralvalues and literacy. These skills include: critical thinking, creative thinking, clearcommunication skills, listening skills, and good moral habits.